Implementasi Literasi dalam Pembelajaran Statistik Menggunakan Modul Berbasis Kecerdasan Linguistik - Kirom, Sabitul (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2019)
Literacy activities are difficult elements to separate in various current activities. Literacy activities play an important role in realizing the development of education and culture that are characterized by increasing productivity and competitiveness. This study aims to describe the implementation of literacy in statistical learning using modules based on linguistic intelligence. The focus of this study includes three main points, namely (1) learning design, (2) implementation of learning, (3) and evaluation of learning. The method used in this study is a qualitative research method. The results of this study are as follows. First, the literacy aspect has been implemented in the learning design documented in the Syllabus, RPS, RPP, and Lecture Contract. Secondly, the literacy aspect has been implemented in the implementation of learning which is reflected through activities in the learning process. Third, aspects of literacy have been implemented in the evaluation of learning documented in assignments and practice questions. The results of this study have a positive impact on enriching the repertoire of research, specifically related to the implementation of literacy in learning. Thus, it can be concluded that the literacy aspect has been implemented in statistical learning using modules based on linguistic intelligence, starting from the learning design, learning implementation, and learning evaluation.